1996
DOI: 10.2307/5883
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of the Distribution of Tsetse Flies in the Lambwe Valley, Kenya, Using Landsat TM Satellite Imagery and GIS

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. Satellite imagery, geographic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 28 publications
0
50
0
1
Order By: Relevance
“…However, few studies relating vector distribution to satellite data have addressed the problem of spatial correlation in the data sets. A rare exception is a study undertaken by Kitron and others, 21 who undertook a spatial analysis of tsetse fly distribution in the Lambwe Valley of Kenya using Landsat Thematic Mapper (TM) imagery and a GIS. They found that using multiple regression analysis, they could explain 87% of the variance in fly density using several TM bands.…”
mentioning
confidence: 99%
“…However, few studies relating vector distribution to satellite data have addressed the problem of spatial correlation in the data sets. A rare exception is a study undertaken by Kitron and others, 21 who undertook a spatial analysis of tsetse fly distribution in the Lambwe Valley of Kenya using Landsat Thematic Mapper (TM) imagery and a GIS. They found that using multiple regression analysis, they could explain 87% of the variance in fly density using several TM bands.…”
mentioning
confidence: 99%
“…An alternative approach is to use landscape variables derived from remote sensing satellites as predictors, with or without incorporating the effects of spatial dependence. Pertinent examples include vectors of Eastern equine encephalomyelitis (Moncayo et al 2000), tick vectors of Lyme disease (Brownstein et al 2003, Guerra et al 2001, Kitron et al 1996, sand fly vectors of leishmaniasis (Cross et al 1996, Elnaiem et al 2003, Miranda et al 1998, Thomson et al 1999, tse-tse fly vectors of African trypanosomiasis (Kitron et al 1996, Rogers 2000, and mosquito vectors of malaria (Beck et al 1994, Diuk-Wasser et al 2004, Thomson et al 1996, Wood et al 1991a,b, 1992. Of these models, however, only a few have been validated with an independent dataset (Beck et al 1997, Brownstein et al 2004).…”
Section: Introduction Wmentioning
confidence: 99%
“…Images obtained from these satellites have a relatively small scene sizes (60-176 km 2 ) and are therefore suitable for relatively small study areas. They have proved to be most useful for local landscape studies of vector habitats, breeding and/or resting sites, where all information is derived from a single satellite image (Kitron et al, 1996;Dister et al, 1997).…”
Section: Sample Sitementioning
confidence: 99%